Electron paramagnetic resonance analysis of a transient species formed during water oxidation catalyzed by the complex ion [(bpy)2Ru(OH2)]2O(4+) - Stull, Jamie A; Stich, Troy A; Hurst, James K; Britt, R David (Inorganic chemistry, 2013)
The ruthenium "blue dimer" [(bpy)2Ru(OH2)]2O(4+)--the first well-defined molecular complex able to catalyze water oxidation at low overpotentials--has been the subject of numerous experimental and computational studies. However, elements of the reaction mechanism remain controversial. Of particular interest is the nature of the O-O bond-forming step. Herein, we report the first advanced electron paramagnetic resonance (EPR) spectroscopic studies of a high-valent intermediate that appears under conditions in which the catalyst is actively turning over. Results from previous studies have suggested that this intermediate is derived from [(bpy)2Ru(V)(O)]2O(4+), denoted {5,5}. Under photooxidizing conditions, the corresponding EPR signal disappears at a rate comparable to the turnover rate of the catalyst once the illumination source is removed. In the present work, the electronic and geometric structures of this species were explored using a variety of EPR techniques. Continuous wave (CW) EPR spectroscopy was used to probe the hyperfine coupling of the Ru ions, while corresponding ligand (14)N hyperfine couplings were characterized with electron spin echo envelope modulation (ESEEM) and hyperfine sublevel correlation spectroscopy (HYSCORE) methods. Finally, (1)H/(2)H ENDOR was performed to monitor any exchangeable protons. Our studies strongly suggest that the accumulating transient is an S = 1/2 species. This spin state formulation of the so-called {5,5} species is consistent with only a limited number of electronic structures, each of which is discussed. Notably, the observed large metal hyperfine coupling indicates that the orbital carrying the unpaired spin has significant ruthenyl-oxyl character, contrary to an earlier electronic structure description that had tentatively assigned the signal to formation of a bipyridine ligand radical.